Enhancing the properties and performance of polysulfone ultrafiltration membranes using citric acid based deep eutectic solvent additives - Yousef Elhamarnah (17869382) (2024)
This study focuses on improving the performance of polysulfone (PSF) membranes through modification with a Deep Eutectic Solvent (DES) composed of Citric Acid (CA) and Choline Chloride (ChCl). Various concentrations, ranging from 1.00 wt% to 4.00 wt%, were explored to investigate the impact of DES on membrane properties. The membranes underwent morphological analysis using Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Fourier-transform Infrared Spectroscopy (FTIR) was utilized to understand chemical interactions, while mechanical strength and contact angle assessments provided insights into the physical robustness and hydrophilicity of the membrane surfaces. Zeta potential measurements revealed an increase in negative surface charge, particularly notable at 1.00 wt% and 2.00 wt% CA concentrations, which significantly enhanced dye rejection capabilities. Leaching tests were conducted to ensure the environmental integrity of the DES within the membrane structure. The performance metrics of the membranes, including pure water permeability (PWP) and dye rejection, were thoroughly evaluated. Although the 3.00 wt% CA-DES membranes showed high PWP, the 2.00 wt% CA-DES membranes demonstrated the best overall performance, achieving a commendable balance between high water flux, dye rejection, and antifouling properties, with an FRR of 93 %. The Thermal Gravimetric Analysis (TGA) highlighted variations in thermal stability. This study identifies the 2.00 wt% CA-DES modified PSF membrane as the superior choice, offering an unparalleled combination of permeability, selectivity, and antifouling properties. The advancements represented by this membrane mark a significant stride forward in the application of ultrafiltration technology, potentially impacting a wide range of industrial and environmental processes. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2024.112110